Penerapan Teknologi Artificial Intelligence Sebagai Media Inovatif dalam Mendukung Proses Pembelajaran dan Kreativitas Siswa Paket C di PKBM Bangkit Kota Semarang - Fikriah, Fari Katul; Ariyanto, Amelia Devi Putri (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
The rapid development of information technology requires educational institutions, including Community Learning Activity Centers (PKBM), to innovate in improving the quality of learning and fostering student creativity. PKBM Bangkit Kota Semarang as a non-formal educational institution still faces obstacles in the form of low learning motivation and limited technology-based learning media. This community service activity aims to design and implement Artificial Intelligence (AI) technology as an innovative media to support the learning process and encourage the creativity of Package C students. The implementation method includes identifying partner needs, designing and developing AI media, training and mentoring, implementing in class, and monitoring and evaluation. The results of the community service show that AI-based learning media has succeeded in increasing learning participation, facilitating access to materials, encouraging independent learning, and receiving positive responses from tutors and students. These findings demonstrate that the application of AI in PKBM has the potential to be an innovative solution for strengthening the quality of non-formal education in the digital era.